Evaluasi Sistem Proteksi dan Koordinasi Relai Arus lebih Gedung Mall XYZ Menggunakan ETAP 19.0.1 - Fuad Djauhari; Idris Kusuma; Endang Retno Nugroho (Universitas Nasional, 2022)
Large buildings require optimal electrical protection. Short-circuit events are the most common occurrences. If there is a short-circuit fault on one of the feeders, the circuit breaker whose position is upstream from the fault center must work ahead of the circuit breaker whose position is upstream from the short-circuit fault center. The problem that occurs in the XYZ Mall Building is the opposite. When there is a short circuit current, it will cut off the main connector. As a result, some of the building's electricity will also go out. The purpose of this study is to regulate the coordination of relay protection repeatedly in this building. The study will evaluate the existing electrical Single Line Diagram of the XYZ Mall Building and perform simulations with the help of ETAP 19.0.1 software. The simulation results get the value of the protection system that has been adjusted where the curves of each relay do not intersect with each other so that the coordination of each relay is safe, with the standard time delay setting of 0.2 to 0.4 seconds. To overcome the problem in the XYZ Mall building, the relay that is not suitable must be set manually according to the simulation results to prevent tripping some of the buildings in the event of a short circuit fault.